Standar Penyelenggaraan Pendidikan Nasional - Muhamad Dini Handoko (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
The standard of the educational process is the national standard of education, which means that a standard in the management of the educational process must be met by every formal educational institution at a certain level of education in providing services to the community wherever the educational institution is located nationally. Process standards are associated with the implementation of learning, which means the standard of the educational process contains how the learning process should take place in each educational unit carried out by every teacher, both class teachers and subject teachers, so that the quality of learning can be carried out optimally. The condition of inequality in the quality of education is caused by the non-standard quality of learning. The standard evaluation of the learning assessment process uses an authentic assessment approach.